2011
DOI: 10.1021/bc200147m
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Cell Surface Functionalization of Human Fetal Osteoblasts for Tissue Engineering

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…However, the adhesion of human bone-derived cells onto the large pore scaffolds was not rapid enough to ensure the optimal cellularization of these scaffolds. Combining our previous observations that alumina-based scaffolds can be chemically functionalized with gallate-based ligands, 27 and that human fetal osteoblasts can be chemically functionalized using biocompatible click chemistry, 28 we showed here that the number of human fetal osteoblasts adhering to the scaffolds can be enhanced by their covalent binding to the scaffolds using an hetero-bifunctional ligand and biocompatible click-chemistry. Therefore, we show here that large-pore alumina-based scaffolds and primary human fetal cells derived from the fetal bones To define the diameters of the pores and pore-openings, SEM micrographs at low magnifications were analyzed (grey bars) using the software Linear Intercept, then the cumulative values were calculated (solid lines).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the adhesion of human bone-derived cells onto the large pore scaffolds was not rapid enough to ensure the optimal cellularization of these scaffolds. Combining our previous observations that alumina-based scaffolds can be chemically functionalized with gallate-based ligands, 27 and that human fetal osteoblasts can be chemically functionalized using biocompatible click chemistry, 28 we showed here that the number of human fetal osteoblasts adhering to the scaffolds can be enhanced by their covalent binding to the scaffolds using an hetero-bifunctional ligand and biocompatible click-chemistry. Therefore, we show here that large-pore alumina-based scaffolds and primary human fetal cells derived from the fetal bones To define the diameters of the pores and pore-openings, SEM micrographs at low magnifications were analyzed (grey bars) using the software Linear Intercept, then the cumulative values were calculated (solid lines).…”
Section: Discussionsupporting
confidence: 78%
“…27 We have also previously shown that human fetal osteoblasts can be chemically functionalized using biocompatible click chemistry. 28 Thus, in order to enhance the adhesion of the fetal osteoblasts to the scaffold, we combined these two approaches by designing and synthesizing (Scheme 1) compound 5, an hetero-bifunctional ligand bearing a gallate functionality and an activated alkyne. The alumina scaffolds were functionalized with compound 5, then the azido-modified human fetal osteoblasts (10 6 cells per scaffold) were added to scaffolds which were either unfunctionalized or had been pre-functionalized with compound 5 (5 or 10 μM).…”
Section: Click-functionalization Of the Scaffolds And Adhesion Of Hummentioning
confidence: 99%
“…10-Deacetylbaccatin III was obtained from Indena, SpA, Italy. 10-Cyclopropanecarbonyl-10-deacetyl-2-debenzoyl-2-(3-fluorobenzonyl)-7-triethylsilylbaccatin III ( 5 ) [35], (3 R ,4 S )-1- tert -butoxycarbonyl-3-triisoproylsilyloxy-4-(2-methyl-1-propenyl)-2-azetidinone ( 6 ) [39], 5-fluoro-3 H –benzo[ b ]thiophene ( 8 ) [40], triisopropylsilyl 4-(pyridine-2-yldisulfanyl)pentanoate ( 11 ) [5], biotinylhydrazine ( 16 ) [42], 10-deacetyl-2-debenzoyl-7,10,13-tris(triethylsilyl)baccatin III ( 17 ) [35], (3 R ,4 R )-1-( tert -butoxycarbonyl)-3-triisopropylsiloxy-4-trifluoromethylazetidin-2-one ( 22 ) [43], 2-(5-oxo-triisopropylsiloxypentan-2-yl)disulfanylphenylacetic acid ( 24 ) [5], and biotinyl-NH(PEG) 3 (CH 2 ) 2 -NH 2 ( 27 ) [45] were prepared according to literature methods. Human peripheral blood plasma (HemaCare), 0.9% sodium chloride injection saline with 10% dextrose (Baxter Healthcare Corp.), RPMI cell culture medium, and phosphate-buffered saline (PBS) (Gibco) were used as received for formulation and NMR-based assays.…”
Section: Methodsmentioning
confidence: 99%
“…Phenotypic maturation in vivo was shown to not carry the immune privileges of therapeutic FPCs in rodent models (Hausherr et al, 2017). Chemical functionalization (e.g., click chemistry, bioorthogonal chemical reactions, covalent binding) of therapeutic cell surfaces allows optimal conjugation with bioengineered scaffolds, while maintaining and optimizing cellular viability, adhesion, persistence, and function (Borcard et al, 2011(Borcard et al, , 2012Comas et al, 2012;Krauss Juillerat et al, 2012). Optimal mechanical properties and efficient vascularization capacity of implanted constructs are essential, while biodegradable hydrogels may enable local cell maintenance (Tenorio et al, 2011;Amini et al, 2012).…”
Section: Bone Fpc Modulation and Drug Deliverymentioning
confidence: 99%